Methods to improve the translation of evidence-based interventions: A primer on dissemination and implementation science for occupational safety and health researchers and practitioners. (August 2022) - Guerin, R.J.; Glasgow, R.E.; Tyler, A.; Rabin, B.A.; Huebschmann, A.G.
Highlights: A research-to-practice gap in occupational safety & health (OSH) persists. This gap reduces adoption/use of evidence-based interventions protecting workers. Dissemination & implementation (D&I) science bridges the research-to-practice gap. D&I approaches involve beneficiaries and could address complex, OSH challenges. This primer provides resources to help build D&I capacity among OSH researchers. Abstract: Objective: A limited focus on dissemination and implementation (D&I) science has hindered the uptake of evidence-based interventions (EBIs) that reduce workplace morbidity and mortality. D&I science methods can be used in the occupational safety and health (OSH) field to advance the adoption, implementation, and sustainment of EBIs for complex workplaces. These approaches should be responsive to contextual factors, including the needs of partners and beneficiaries (such as employers, employees, and intermediaries). Methods: By synthesizing seminal literature and texts and leveraging our collective knowledge as D&I science and/or OSH researchers, we developed a D&I science primer for OSH. First, we provide an overview of common D&I terminology and concepts. Second, we describe several key and evolving issues in D&I science: balancing adaptation with intervention fidelity and specifying implementation outcomes and strategies. Next, we review D&I theories, models, and frameworks and offer examples for applying these to OSH research. We also discuss widely used D&I research designs, methods, and measures. Finally, we discuss future directions for D&I science application to OSH and provide resources for further exploration. Results: We compiled a D&I science primer for OSH appropriate for practitioners and evaluators, especially those newer to the field. Conclusion: This article fills a gap in the OSH research by providing an overview of D&I science to enhance understanding of key concepts, issues, models, designs, methods and measures for the translation into practice of effective OSH interventions to advance the safety, health and well-being of workers.